Testing of Plant Growth Regulator and Organic Fertilizers on Black Rice Plants - Asrijal Asrijal; Sukriming Sapareng; Ambo Upe; Akmal Akmal; Taruna Shafa Arzan AR (The University of Lampung, 2023)
One effort to increase food security is to increase rice production by providing adequate nutrition to rice plants with organic fertilizers and growth regulators (PGR). The aim of this study was to measure the growth and production of black rice (black oryza), as well as the distribution of the average plus or minus data through the treatment of various concentrations of PGR and doses of organic fertilizer. The research design was a two-factor factorial randomized block design. The first factor of PGR concentration (Z) consisting of 5, namely 0 (Z0), 1 (Z1), 1.5 (Z2), 2 (Z3) and 2.5 (Z4) ml/L of water. The second factor of organic fertilizer (P) consisting of 5, namely 0 (P0), 1 (P1), 2 (P2), 3 (P3) and 4 (P4) tons/ha. The treatment was repeated 5 times so that 125 experimental units were provided. The best grain yield 47.03 g/panicle was resulted from a single effect of PGR treatment at a concentration of 2 ml/L, whereas single treatment using organic fertilizer at a dose of 4 ton/ha produced grain of 46.23 g/panicle. The best combination of PGR concentration of 2 ml/L of water with organic fertilizer 4 tons/ha, resulted the highest grain yield of 50.24 g/panicle, equivalent to average dry harvested grain of 5.02 ton/ha or 3.26 ton/ha of dry unhusked grain. The distribution of the average plus minus data is good with a low average distribution for all measurement components. Keywords: Black Cempo, Harvested Dry Rice, Dry Unhulled Grain, Growth Hormone, Nutrition